Cestodes (Caryophyllidea) of the stinging catfish Heteropneustes fossilis (Siluriformes: Heteropneustidae) from Asia - Ash, Anirban; Scholz, Tomáš; Oros, Mikuláš; Levron, Céline; Kar, Pradip Kumar (The Journal of parasitology, 2011)
The stinging catfish Heteropneustes fossilis (Bloch) (Siluriformes: Heteropneustidae) has been reported to harbor as many as 19 species of caryophyllidean tapeworms (Cestoda) of 11 genera in tropical Asia (Indomalayan zoogeographical region). However, a critical review of the species composition has shown that only 1 species, Lucknowia fossilisi Gupta, 1961 (Lytocestidae), is a specific parasite of H. fossilis. Three other species, Djombangia penetrans Bovien, 1926 (syn., Djombangia caballeroi Sahay and Sahay, 1977 ), Pseudocaryophyllaeus ritai Gupta and Singh, 1983 (syn. Pseudocaryophyllaeus lucknowensis Gupta and Sinha, 1984 ), and Pseudocaryophyllaeus tenuicollis (Bovien, 1926) Ash, Scholz, Oros and Kar, 2011 (syn. P. mackiewiczi Gupta and Parmar, 1982 ), were found only once. Lucknowia fossilisi is redescribed on the basis of new material collected in West Bengal and voucher specimens from Maharashtra, India. A total of 9 species of Capingentoides, Lucknowia, Lytocestus, Pseudoadenoscolex, Pseudocaryophyllaeus, Pseudoheteroinverta, and Sukhapatae are newly synonymized with L. fossilisi and previous synonymies of 9 other species, proposed by Hafeezulah (1993), are confirmed. Generic diagnosis of Lucknowia Gupta, 1961 is amended. In addition, 1 species of Pseudobatrachus and 2 species of the monotypic genera Pseudoneckinverta and Sudhaena are invalidated as nomina nuda.
Keywords: Bangladéš; nemoci ryb; sumci; Indie; Cestode Infections; Fish Diseases; prevalence; Catfishes; Microscopy, Electron, Scanning; zvířata; mikroskopie elektronová rastrovací; cestodózy; transmisní elektronová mikroskopie; India; Microscopy, Electron, Transmission; Prevalence; Animals; Bangladesh; Cestoda